HUBUNGAN KUALITAS KARET RAKYAT DENGAN TAMBAHAN PENDAPATAN PETANI DI DESA PROGRAM DAN NON-PROGRAM - Sannia, Belladina; Ismono, R. Hanung; Viantimala, Begem (Lampung University, 2013)
This study compared the quality of rubber between the villages of rural development programs and nonrubberdevelopment program. This study that of describe the socio-economic characteristics of the farm andrubber farmers, identify farmers efforts to improve the quality of rubber produced, as well as analyze theincrease of rubber farm income gains due to the efforts to improve the quality of rubber in particular the useof formic acid as a latex coagulant. The method used in this study is a quantitative analysis method, themethod of calculation income of farmers and rubber farmers profits calculation. Research location are theprogram village (Lesung Bhakti) and non-program village (Pagar Jaya). Respondents used in this studyabout 85 people, divided by 45 villages program and 40 non-program villages. From the analysis resultswere found that the program village has a higher added income than that of non-program villages. As resultshows that farmers that do increase of rubber quality earn extra income than the farmers that do notincrease activities rubber quality.